Determinant of Job Satisfaction and Organization Citizenship Behavior in Dki Jakarta Hospital Government - Zami, Alex; Widyayani, Fransisca Anri; Kasbuntoro, Kasbuntoro (International Review of Management and Marketing, 2019)
The purpose of this research is to find out and to prove empirically whether Transformational Leadership and nursing workload to job satisfaction and its implications on organization citizenship behavior (OCB) nursing DKI Jakarta Hospital Government. To find answers to these questions, there were 7 hypothesis in this study: Transformational Leadership and nursing workload or entirely have an influence on the job satisfaction of nursing DKI Jakarta Hospital Government, as well as the style of Transformational Leadership, nursing workload and job satisfaction partially or entirely affect the organization citizenship behavior (OCB) of nursing DKI Jakarta Hospital Government. The research method was descriptive verification, with a total population of 731 nursing. Number of samples obtained by the method of estimation using rule of thumb with calculation of 5 x 43 = 215 respondents. Where as the research instrument used is observation, literature study and questionnaire. With questionnaire scoring using Likert scale 1 to 5. The analysis technique used was descriptive statistical analysis to describe the data collected without intending to create generally accepted conclusions or generalization. Descriptive analysis was performed using SPSS 22.00 program. The model used in this study was a model of causality or correlation effect. To test the hypothesis proposed in this study, the analysis technique used was Structural Equation Modeling (SEM), operated through LISREL 8.70 program. Based on the analysis, this study used Sub-Structural Equation of R2 0.44 or 44% and Structural Equation of R2 0.70 or 70%, while 30% is affected by other variables that were not explored in this research. Therefore, it was proven that the transformational leadership, nursing workload and job satisfaction significantly influenced partially or entirely organization citizenship behavior (OCB) of nursing DKI Jakarta Hospital Government. Keywords: Transformasional Leadership, Nursing Workload, Job Satisfaction and Organization Citizenship Behavior JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7658